De novo coding variants in the AGO1 gene cause a neurodevelopmental disorder with intellectual disability - Schalk, Audrey; Cousin, Margot A.; Challman, Thomas D.; Wain, Karen E.; Powis, Zoe; Minks, Kelly; Trimouille, Aurelien; Lasseaux, Eulalie; Lacombre, Didier; Angelini, Chloe; Michaud, Vincent; Van-Gils, Julien; et al. (Journal of Medical Genetics, 2021)
Background High-impact pathogenic variants in more than a thousand genes are involved in Mendelian forms of neurodevelopmental disorders (NDD). Methods This study describes the molecular and clinical characterisation of 28 probands with NDD harbouring heterozygous AGO1 coding variants, occurring de novo for all those whose transmission could have been verified (26/28). Results A total of 15 unique variants leading to amino acid changes or deletions were identified: 12 missense variants, two in-frame deletions of one codon, and one canonical splice variant leading to a deletion of two amino acid residues. Recurrently identified variants were present in several unrelated individuals: p.(Phe180del), p.(Leu190Pro), p.(Leu190Arg), p.(Gly199Ser), p.(Val254Ile) and p.(Glu376del). AGO1 encodes the Argonaute 1 protein, which functions in gene-silencing pathways mediated by small non-coding RNAs. Three-dimensional protein structure predictions suggest that these variants might alter the flexibility of the AGO1 linker domains, which likely would impair its function in mRNA processing. Affected individuals present with intellectual disability of varying severity, as well as speech and motor delay, autistic behaviour and additional behavioural manifestations. Conclusion Our study establishes that de novo coding variants in AGO1 are involved in a novel monogenic form of NDD, highly similar to the recently reported AGO2-related NDD.
CRIS-Team WoS Importer:2021-12-24